Integrated omics analyses reveal the details of metabolic adaptation of Clostridium thermocellum to lignocellulose-derived growth inhibitors released during the deconstruction of switchgrass. Issue 1 (December 2017) - Poudel, Suresh; Giannone, Richard; Rodriguez, Miguel; Raman, Babu; Martin, Madhavi; Engle, Nancy; Mielenz, Jonathan; Nookaew, Intawat; Brown, Steven; Tschaplinski, Timothy; Ussery, David; Hettich, Robert
Abstract Background Clostridium thermocellum is capable of solubilizing and converting lignocellulosic biomass into ethanol. Although much of the work-to-date has centered on characterizing this microbe's growth on model cellulosic substrates, such as cellobiose, Avicel, or filter paper, it is vitally important to understand its metabolism on more complex, lignocellulosic substrates to identify relevant industrial bottlenecks that could undermine efficient biofuel production. To this end, we have examined a time course progression ofC. thermocellum grown on switchgrass to assess the metabolic and protein changes that occur during the conversion of plant biomass to ethanol. Results The most striking feature of the metabolome was the observed accumulation of long-chain, branched fatty acids over time, implying an adaptive restructuring ofC. thermocellum's cellular membrane as the culture progresses. This is undoubtedly a response to the gradual accumulation of lignocellulose-derived inhibitory compounds as the organism deconstructs the switchgrass to access the embedded cellulose. Corroborating the metabolomics data, proteomic analysis revealed a corresponding time-dependent increase in various enzymes, including those involved in the interconversion of branched amino acids valine, leucine, and isoleucine to iso- and anteiso-fatty acid precursors. Additionally, the metabolic accumulation of hemicellulose-derived sugars and sugar alcohols concomitant with increased abundance of enzymes involved in C5 sugar metabolism/pentose phosphate pathway indicates thatC. thermocellum shifts glycolytic intermediates to alternate pathways to modulate overall carbon flux in response to C5 sugar metabolites that increase during lignocellulose deconstruction. Conclusions Integrated omic platforms provided complementary systems biological information that highlightC. thermocellum 's specific response to cytotoxic inhibitors released during the deconstruction and utilization of switchgrass. These additional viewpoints allowed us to fully realize the level to which the organism adapts to an increasingly challenging culture environment—information that will prove critical toC. thermocellum 's industrial efficacy.